A Bibliometric analysis of folate receptor research - Cari A. Didion; Walter A. Henne (BMC Cancer, 2020)
Abstract Background The objective of this study was to conduct a bibliometric analysis of the entire field of folate receptor research. Folate receptor is expressed on a wide variety of cancers and certain immune cells. Methods A Web of Science search was performed on folate receptor or folate binding protein (1969-to June 28, 2019). The following information was examined: publications per year, overall citations, top 10 authors, top 10 institutions, top 10 cited articles, top 10 countries, co-author collaborations and key areas of research. Results In total, 3248 documents for folate receptor or folate binding protein were retrieved for the study years outlined in the methods section search query. The range was 1 per year in 1969 to 264 for the last full year studied (2018). A total of 123,720 citations for the 3248 documents retrieved represented a mean citation rate per article of 38.09 and range of 1667 citations (range 0 to 1667). Researchers in 71 countries authored publications analyzed in this study. The US was the leader in publications and had the highest ranking institution. The top 10 articles have been cited 7270 times during the time frame of this study. The top cited article had an average citation rate of 110 citations per year. Network maps revealed considerable co-authorship among several of the top 10 authors. Conclusion Our study presents several important insights into the features and impact of folate receptor research. To our knowledge, this is the first bibliometric analysis of folate receptor.